1998
DOI: 10.1055/s-2006-957528
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Sesquiterpene Lactones fromSaussurea lappaon Tumor Necrosis Factor-α Production in Murine Macrophage-Like Cells

Abstract: Total methanol extract of Saussurea lappa radix (Compositae) showed potent inhibitory effect on the production of tumor necrosis factor-alpha (TNF-alpha), a proinflammatory cytokine, in murine macrophage-like cell (RAW264.7 cells) in our previous screening studies on 120 Korean medicinal plants. The activity-guided purification of the plant resulted in the isolation of three components. The chemical structures of the components isolated were established by spectroscopic analyses as sesquiterpene lactones [cyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 7 publications
1
60
0
1
Order By: Relevance
“…Cheng and co-workers 15) reported a possible central neurotoxic effect for this compound isolated from Centaurea solstitialis, while Hay and co-workers 16) showed that cynaropicrin inhibited aortic smooth muscle contractility, also suggesting a toxic pharmacological profile. Cho and coworkers 17) demonstrated that cynaropicrin exhibits inhibitory effects on the production of tumor necrosis factor-a (TNFa), a proinflammatory cytokine. Recently, its antihyperlipidemic, 18) anticancer 19) trypanocidal and antimicrobial 20) activities were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Cheng and co-workers 15) reported a possible central neurotoxic effect for this compound isolated from Centaurea solstitialis, while Hay and co-workers 16) showed that cynaropicrin inhibited aortic smooth muscle contractility, also suggesting a toxic pharmacological profile. Cho and coworkers 17) demonstrated that cynaropicrin exhibits inhibitory effects on the production of tumor necrosis factor-a (TNFa), a proinflammatory cytokine. Recently, its antihyperlipidemic, 18) anticancer 19) trypanocidal and antimicrobial 20) activities were reported.…”
Section: Resultsmentioning
confidence: 99%
“…1,7,18) Several previous studies have demonstrated that these herbs exhibited anti-tumor activities. [1][2][3][4][5] In the present study, we analyzed effects of Saussurea lappa, Pharbitis nil, Plantago asiatica and Taraxacum mongolicum on proliferation and apoptosis of a human gastric cancer cell line AGS. Our cell proliferation assay showed that Saussurea lappa and Pharbitis nil strongly inhibited cell proliferation of AGS, whereas Plantago asiatica and Taraxacum mongolicum exhibited no detectable effects on cellular growth (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also demonstrated that Saussurea lappa exhibits anti-tumor and anti-ulcer activity as well as anti-inflammatory effects via down-regulation of tumor necrosis factor-a, [1][2][3][4][5] and that Pharbitis nil has the antifungal effects by antifungal peptides. 6) Plantago asiatica and Taraxacum mongolicum have been widely used to treat for cancers and liver diseases and were reported to carry immune suppressive effects.…”
Section: Saussurea Lappa Pharbitis Nil Plantago Asiatica Andmentioning
confidence: 99%
“…In the case of cynaropicrin (162) the result was better than dbcAMP and prednisolone used as controls. Treatment with sulfydryl (SH) compounds such as L-cysteine, dithiothreitol, and 2-mercaptoethanol abrogated the inhibitory effect of cynaropicrin on TNF-a production showing that M. Bruno et al / Phytochemistry xxx (2013) xxx-xxx 59 the bioactive moiety is the unsaturated lactone (Cho et al, 2000(Cho et al, , 1998. Cynaropicrin (162), aguerin B (160) and grosheimin (264) showed a remarkable inhibitory effect on inducible nitric oxide synthase with IC 50 values in the range 1.5-9.5 lg/mL (Blunder et al, 2008).…”
Section: Anti-inflammatorymentioning
confidence: 99%